Effects of ultrasound pretreatment on the enzymolysis of pectin: Kinetic study, structural characteristics and anti-cancer activity of the hydrolysates. (June 2018) - Ma, Xiaobin; Wang, Danli; Chen, Weijun; Ismail, Balarabe Bilyaminu; Wang, Wenjun; Lv, Ruiling; Ding, Tian; Ye, Xingqian; Liu, Donghong
Abstract: In this study, the effects of ultrasound pretreatment on the enzymolysis of pectin were investigated. Ultrasound at an intensity of 18.0 W mL −1 for 30 min significantly decreased pectin molecular weight by 50.50%, whereas it increased the degree of hydrolysis (DH) for enzymatic reactions by 20.22%. After ultrasound treatment, the maximum velocity of the enzymatic reaction (Vmax ) increased but the Michaelis constant (Km ) decreased, indicating an improved enzymolysis efficiency and stronger affinity between pectin and pectinase. Investigations into pectin structures demonstrated that, ultrasound effectively decreased the degree of methoxylation (DM) resulting in more favorable substrates for enzymatic attack; thus, the homogalacturonan (HG) regions of the pretreated pectin were more completely degraded during enzymolysis compared with the control. According to the results of FT-IR and NMR analysis, both ultrasound and pectinase had no effect on pectin primary structures. However, ultrasound pretreatment could induce higher content of galactose in pectin hydrolysates, which contributed to an improved inhibitory activity against HT-29 colon cancer cells as shown by MTT assay. Graphical abstract: Image 1 Highlights: Ultrasound pretreatment improved the enzymatic degradation of pectin. The Vmax increased but the Km decreased after ultrasound pretreatment. The degree of methylation (DM) of pectin significantly decreased under ultrasound. Hydrolysates of the pretreated pectin had higher galactose content. Hydrolysates of the pretreated pectin had higher anti-cancer activity.